Meaning-in-Life Orientations in Individuals With Different Levels of Fear of Death - Полина Р. Дмитриева (Rossijskij psihologičeskij žurnal., 2020)
Introduction. This paper examines meaning-in-life orientations in individuals with different levels of fear of death and provides a theoretical overview of the phenomenon of death in the context of studies of meaning-in-life orientations. Attitudes towards death and their associations with the value and meaning sphere are insufficiently developed in Russian psychological studies. The phenomenon of death should be studied in the context of meaningfulness of life and the formation of a conscious attitude towards life. This study is first to examine associations among the meaningfulness of life, life satisfaction, and attitudes towards death in individuals for whom the issues of death and dying are not relevant in their current life situation. Methods. These were psychodiagnostic techniques, including the Life Satisfaction questionnaire, the Meaning-in-Life Orientations test, MLO (Russian-language version of the Purpose-in-Life Test modified by D. A. Leont'ev), and the Death Attitude Profile-Revised (a modified version by T. A. Gavrilova) and methods of mathematical statistics for data processing (descriptive statistics, Pearson’s correlation coefficient, and Mann–Whitney test). Results. This section contains data from an empirical study involving 148 individual participants aged 18–50 years. The findings indicate that respondents with a high level of fear of death are characterized by a lower level of vital involvement and meaningfulness of life. Discussion. The results suggest that there are associations between the level of fear of death and meaning-in-life orientations. Significant differences in the levels of vital involvement, meaningfulness of life, and attitudes towards death were found among individuals with different levels of fear of death. Attitudes towards death are directly related to the meaningfulness of life and life satisfaction.